Differences in effectiveness of membrane fixation using periosteal vertical mattress and simple sling suture techniques in infrabony pocket treatment - Beta Widya Oktiani; Sri Pramestri Lastianny; Ahmad Syaify (Majalah Kedokteran Gigi Indonesia, 2019)
Guide tissue regeneration (GTR) is the treatment of infrabony pockets for soft and hard tissue regeneration. Membrane is used as a barrier and prevents apical migration of the cells in epithelial tissues. Membrane fixation is one of the procedures in GTR treatment because resorbed membrane is less stable. Simple sling suture technique for membrane fixation has 1 anchorage, located in coronal flap, while periosteal vertical mattress suture technique has 2 anchorages in periosteum, making it more stable. This study aimed to study the differences in the effectiveness of membrane fixation using periosteal vertical mattress suture and simple sling suture techniques in terms of probing depth, relative attachment loss, and alveolar bone height in the treatment of infrabony pockets. The samples were divided into 2 groups. The first group was open flap debridement (OFD) with demineralized freeze dried bone allograft (DFDBA) application and membrane fixation with simple sling suture, while the second group was OFD with DFDBA application and membrane fixation with periosteal vertical mattress suture, observed on day 0, 30th day, and 90th day. The results of the study showed significant differences in the probing depth and relative attachment loss (except from the 30th day to the 90th day), and there were no significant differences in the alveolar bone height from the baseline to the 90th day, between the group of membrane fixation using simple sling suture and that of periosteal vertical mattress suture techniques on flap surgery. This study concluded that membrane fixation in the treatment of infrabony pocket with periosteal vertical mattress suture technique is more effective in reducing the probing depth and relative attachment loss, but there is no difference in increasing the alveolar bone height when compared to simple sling suture technique.